2016
DOI: 10.1108/ejim-05-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

The co-creation of multi-agent social innovations

Abstract: Purpose – The research fields of service innovation and social innovation have, until now, been largely disconnected. At the most basic level, a great many social innovations are services, often public sector services with social entrepreneurs organizing and delivering service innovations. As well as this overlap in the focus of research, scholars in both research fields address socio-economic concerns using multidisciplinary perspectives. The purpose of this paper is to provide a framework tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 36 publications
1
56
0
3
Order By: Relevance
“…Hence, these innovations do not occur within a vacuum, but within an entrepreneurial ecosystem [10,52]. Within this entrepreneurial ecosystem, recent studies grant major importance to the social and institutional contexts, because these can provide access to the various types of knowledge that these firms need for the development of social innovations through a process of co-creation [10][11][12][13][14]18]. With respect to the institutional context, Melane-Lavado and Álvarez-Herranz [13] found that universities can provide knowledge regarding unsatisfied social demands and regarding how to meet these demands from a sustainability point of view.…”
Section: The Entrepreneurial Ecosystem and Social Innovation In Academentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, these innovations do not occur within a vacuum, but within an entrepreneurial ecosystem [10,52]. Within this entrepreneurial ecosystem, recent studies grant major importance to the social and institutional contexts, because these can provide access to the various types of knowledge that these firms need for the development of social innovations through a process of co-creation [10][11][12][13][14]18]. With respect to the institutional context, Melane-Lavado and Álvarez-Herranz [13] found that universities can provide knowledge regarding unsatisfied social demands and regarding how to meet these demands from a sustainability point of view.…”
Section: The Entrepreneurial Ecosystem and Social Innovation In Academentioning
confidence: 99%
“…With respect to the institutional context, Melane-Lavado and Álvarez-Herranz [13] found that universities can provide knowledge regarding unsatisfied social demands and regarding how to meet these demands from a sustainability point of view. Considering the social context, on the one hand, firms may rely on relationships with customers to access highly specialized market knowledge on the existing or latent needs of society [12]. On the other hand, firms may co-create with their competitors in order to develop innovations focused on social products and services [12].…”
Section: The Entrepreneurial Ecosystem and Social Innovation In Academentioning
confidence: 99%
See 3 more Smart Citations